A Competitive High‐Throughput Screening Platform for Designing Polylactic Acid‐Specific Binding Peptides - Yi Lu; Kai‐Wolfgang Hintzen; Tetiana Kurkina; Yu Ji; Ulrich Schwaneberg (Advanced Science)
Abstract Among biobased polymers, polylactic acid (PLA) is recognized as one of the most promising bioplastics to replace petrochemical‐based polymers. PLA is typically blended with other polymers such as polypropylene (PP) for improved melt processability, thermal stability, and stiffness. A technical challenge in recycling of PLA/PP blends is the sorting/separation of PLA from PP. Material binding peptides (MBPs) can bind to various materials. Engineered MBPs that can bind in a material‐specific manner have a high potential for material‐specific detection or enhanced degradation of PLA in mixed PLA/PP plastics. To obtain a material‐specific MBP for PLA binding (termed PLAbodies), protein engineering of MBP Cg‐Def for improved PLA binding specificity is reported in this work. In detail, a 96‐well microtiter plate based high‐throughput screening system for PLA specific binding (PLABS) was developed and validated in a protein engineering (KnowVolution) campaign. Finally, the Cg‐Def variant V2 (Cg‐Def S19K/K10L/N13H) with a 2.3‐fold improved PLA binding specificity compared to PP was obtained. Contact angle and surface plasmon resonance measurements confirmed improved material‐specific binding of V2 to PLA (1.30‐fold improved PLA surface coverage). The established PLABS screening platform represents a general methodology for designing PLAbodies for applications in detection, sorting, and material‐specific degradation of PLA in mixed plastics.